The effect of polyimide fibre on the tribological properties of polytetrafluoroethylene - Tomina, А.-М.V.; Voloshina, K.R.; Dašić, Predrag; Hranitskyi, Yu. E. (Problems of Tribology, 2025)
The article investigates the effect of discrete polyimide fibre on the tribological properties of polytetrafluoroethylene under friction conditions without lubrication, using the “disk-pad” scheme. It was found that the introduction of 2.5-12.5 vol% filler contributes to a significant increase in the wear resistance of polytetrafluoroethylene, up to 370 times. At the same time, the friction coefficient increases slightly, reaching a maximum value at a fibre content of 7.5 vol%. The decrease in the linear wear intensity of polytetrafluoroethylene is due to an almost twofold increase in hardness. We can explain the improvement in wear resistance by the formation of strong intermolecular bonds at the “matrix-fibre” interface, increased structural uniformity, and the formation of a stable transfer film during friction. Morphological analysis of the friction surfaces confirmed a reduction in the intensity of damage for the filled composites. On the surface of pure polytetrafluoroethylene, traces of plastic deformation, numerous plowing grooves, and signs of micro-cutting were observed, indicating the prevalence of the adhesive-fatigue wear mechanism. In contrast, the composite surfaces are characterized by a smaller number and depth of defects, which suggests a reduced influence of the adhesive component of the friction force and a transition to a pseudo-elastic wear mechanism.For polymer composite materials with an effective fibre content of 7.5 vol%, a set of tribological tests was conducted to determine the critical values of sliding speed and load that affect the linear wear intensity